Chemical composition of green tea (Camellia sinensis) infusions commercialized in Portugal - Reto, Marcia (2015)
To evaluate the potential benefits and risks associated with tea consumption it is important to identify the constituents of this beverage. Levels of some minerals, caffeine and catechins in green tea samples commercialized in Portugal were evaluated. Potassium is the metal present in larger amount (92-151 mg/l). The content of sodium, calcium, fluoride, aluminium, manganese and iron were 35-69, 1.9-3.5, 0.80-2.0, 1.0-2.2, 0.52-1.9, 0.020-0.128 mg/l, respectively. Chromium and selenium were not detected. The resulting data showed considerable variability in catechins content. The levels of epigallocatechin gallate (EGCG) ranged from 117 to 442 mg/l, epicatechin 3-gallate (EGC) from 203 to 471 mg/l, epigallocatechin (ECG) from 16.9 to 150 mg/l, epicatechin (EC) from 25 to 81 mg/l and catechin (C) from 9.03 to 115 mg/l. Caffeine contents in the green tea infusions studied were between 141-338 mg/l. Green tea infusions provide significant amounts of catechins and could be an important source of some minerals.